2021
DOI: 10.3389/fonc.2021.755235
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Blood Index-Based Model to Predict Hepatitis B Virus-Associated Hepatocellular Carcinoma Recurrence After Curative Hepatectomy: Guidance on Adjuvant Transcatheter Arterial Chemoembolization Choice

Abstract: BackgroundPostoperative recurrence is a significant obstacle in hepatocellular carcinoma (HCC) treatment. This study aimed to construct a blood index-based model to predict hepatitis B virus-associated HCC (HBV-HCC) recurrence after curative hepatectomy.MethodsA total of 370 patients who received initially curative hepatectomy for HBV-HCC were included in this study. A novel blood index signature (BIS) was identified and systematically analyzed for its recurrence predictive value. Following this, multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…We therefore selected 200 for subgroup analysis of sample size. Four studies treated patients with HCC with surgery ( 18 , 21 , 22 , 27 ), two studies used TACE treatment ( 20 , 26 ), and one each used sorafenib ( 19 ), radiofrequency ablation (RFA) ( 23 ), sorafenib/immune checkpoint inhibitors (ICIs) ( 24 ), and LT ( 25 ). Nine studies were single-center studies ( 18 , 19 , 21 27 ) and one was a multicenter study ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore selected 200 for subgroup analysis of sample size. Four studies treated patients with HCC with surgery ( 18 , 21 , 22 , 27 ), two studies used TACE treatment ( 20 , 26 ), and one each used sorafenib ( 19 ), radiofrequency ablation (RFA) ( 23 ), sorafenib/immune checkpoint inhibitors (ICIs) ( 24 ), and LT ( 25 ). Nine studies were single-center studies ( 18 , 19 , 21 27 ) and one was a multicenter study ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…We, therefore, used 1.1 for subgroup analysis of cut-off value in the following analyses. Nine articles used the receiver operating characteristic (ROC) curve to determine the best threshold ( 18 22 , 24 27 ) and one study applied the X-tile software ( 23 ). Six studies reported the significance of SIRI in the OS prediction of HCC ( 18 20 , 23 25 ) and eight studies reported the association between SIRI and PFS ( 20 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 We confirmed that MVI was an independent risk factor in this study, which is consistent with our previous findings. 25,26 Our previous studies have demonstrated that receiving adjuvant TACE or HAIC with FOLFOX after hepatectomy might improve the RFS and OS for HCC patients with MVI, and the adverse events were evaluated as mild and manageable. 10,11 SIRI and ANRI are both comprehensive haematological indices of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 23 , 24 Moreover, some models predicting recurrence after PA-TACE for HBV-HCC patients have been developed. 25 , 26 Yet, there is no commendable evaluation system to predict the OS of HBV-HCC who have had PA-TACE directly; therefore, in certain situations, it is difficult for clinicians to decide on initiating PA-TACE, especially for individuals without any significant recurrence risk factors.…”
Section: Introductionmentioning
confidence: 99%